Kerajaan Nasriyyah (1238-1492M) di Granada - Ezad Azraai Jamsari, (Penerbit Universiti Kebangsaan Malaysia, 2004)
There was havoc, chaos and confusion in Spain’s political arena in the 13th and 14th century. Political stability was the dream and wish of each kingdom, both Muslims and Christians. Each party struggled to strengthen its position and influence on others in order to gain absolute power. The Nasrid Kingdom (1238-1492) for example, had put in great effort to sustain and maintain its ruling power as the one and only Islamic power to survive for nearly two and a half centuries. This achievement is perceived as the longest reign of Islamic power in Granada since Islam first set it steps in Spain in the year 711. In the two and a half century period, 22 sultans ruled the Nasrid Kingdom. This article discusses the geographical background of Granada, the political arena in Andalus in the early 13th century and the formation of the Nasrid government, in addition to the duration of power by the sultans which can be divided into three stages, which are the powerful and strengthening era, the glorious and magnificent era, and the declining era and its fall